Validation of a physician global assessment tool for vitiligo extent: Results of an international vitiligo expert meeting. (9th May 2019) - van Geel, Nanja; Wolkerstorfer, Albert; Ezzedine, Khaled; Pandya, Amit G.; Bekkenk, Marcel; Grine, Lynda; Van Belle, Sarah; Lommerts, Janny E.; Hamzavi, Iltefat; Harris, John E.; Eleftheriadou, Viktoria; Esmat, Samia; et al.
Abstract: Currently, vitiligo lacks a validated Physician Global Assessment (PGA) for disease extent. This PGA can be used to stratify and interpret the numeric scores obtained by the Vitiligo Extent Score (VES). We investigated the interrater reliability of a 5‐point PGA scale during an international vitiligo workshop. Vitiligo experts from five different continents rated photographs of non‐segmental vitiligo patients with varying degrees of extent with the PGA score. Good interrater agreements (intraclass correlation coefficient >0.6) were observed between the raters overall and within each continent. All hypotheses to evaluate construct validity were confirmed. Median VES values per category were for limited 1.10 [IQR: 0.21–1.67], moderate 3.17 [IQR: 1.75–6.21], extensive 9.58 [IQR: 6.21–13.03] and very extensive 42.67 [IQR: 21.20–42.67]. Defined categories for vitiligo extent can be valuable for inclusion criteria and may impact future reimbursement criteria.